PENERAPAN BATAS-BATAS WANPRESTASI DAN PERBUATAN MELAWAN HUKUM DALAM PERJANJIAN - Sedyo Prayogo (Jurnal Pembaharuan Hukum, 2016)
The Act of the Civil Law makes a clear distinction between the engagement that is born of the agreement and engagement that is born of the legislation. The legal consequences are born of an engagement agreement is desired by the parties, because memng agreement based on the agreement that a rapprochement between the parties will make arrangements. While the legal consequences of an engagement that is born of a statute may not be desired by the parties, but the relationship of law and the legal consequences prescribed by law. Legal issues that arise in case there is a contractual relationship between the parties and the event of default can filed a lawsuit against the law. Based on the identification and analysis, the authors conclude that the draft Civil Code distinguishes between tort lawsuit is based on the contractual relationship between the Plaintiff and the Defendant and tort claims where there is no contractual relationship between the Plaintiff and the Defendant. Developments in the practice of court decisions indicate that a shift in the theory because of the contractual relationship between the Plaintiff and Defendant did not preclude the filing of a lawsuit against the law.